Predicting climate-related compositional shifts in nut-producing species that are important for bears during hyperphagia - Pérez-Girón, José Carlos; López-Bao, José Vicente; Díaz-Varela, Emilio; Álvarez-Álvarez, Pedro (Frontiers in Forests and Global Change, 2025)
IntroductionClimate change represents an escalating threat to wildlife globally, disrupting ecosystems and altering species interactions. Key nut-producing forest species in the Cantabrian Mountains may be affected, with consequences for Cantabrian brown bears (Ursus arctos) during hyperphagia. Understanding such changes may help to improve conservation strategies to ensure that bears may be able to adapt to changing environmental conditions.MethodsWith this aim, we assessed the current and future habitat suitability of all nut-producing trees in the Cantabrian Mountains. We fitted species distribution models using a down-sampling random forest ensemble approach to create comprehensive maps and species flows, identifying key hotspots of nut production under the SSP3-7.0 and SSP5-8.5 climate change scenarios. Based on bear mobility patterns, we identified areas where individuals lacked access to at least two fruit-producing species, thereby identifying potential areas of nuts shortage for bears during hyperphagia.Results and discussionWe anticipate a potential decline in beech (Fagus sylvatica) and Atlantic oaks (Quercus petraea), with a compositional shift towards thermophilic species, such as sweet chestnuts (Castanea sativa) and Mediterranean oaks (e.g. Quercus ilex). The area unsuitable for any nut-producing species is likely to increase over time, reaching 25% % within the current bear range. The diversity of nut-producing species is projected to decline over time, leaving large areas within the bear’s range with access to only one or two species. Bears may be able to gain access to food resources owing to their dietary plasticity and their ability to move and track energy-rich food resources. Ensuring the long-term accessibility of nuts to bears in some areas could be based on the establishment of Chestnut plantations apart from human settlements, as well as actions to enhance fruiting for oaks, such as the case of Pyrenean oaks.